The incidental finding of otitis media with effusion in children admitted for adenoidectomy or adenotonsillectomy - Luqman Aababaker Mustafa; Said Mustafa Said; Dariya Yousif Azeez; Omar Suad Ali (Advanced Medical Journal)
Background and objectives: Otitis media with effusion is a common condition in the pediatric population, and is a leading cause of hearing loss in this age group. This condition is commonly missed by the parents due to lack of objective symptoms especially in young children, in turn leading to learning difficulties and communication problems. This study focused on the incidental finding of asymptomatic, undiagnosed otitis media with effusion in children with adenotonsillar diseases admitted for adenoidectomy or adenotonsillectomy (aged 2-12 years)